Supramolecular assemblies controlled by cucurbit[n]uril size (n = 6, 7, 8 and 10). (27th February 2020) - Xu, Weitao; Deng, Xinyu; Xiao, Xin; Bian, Bing; Chen, Qing; Dalgarno, Scott J.; Tao, Zhu; Redshaw, Carl
Abstract : The differing cavity size of the Q[ n ] determines the binding interactions between the benzyl substituted 4-pyrrolidinopyridinium salt and each Q[ n ]. Single crystal X-ray diffraction of the guest as well as two host–guest complexes is reported. Abstract : A benzyl substituted 4-pyrrolidinopyridinium salt (G ) with multiple active sites including benzyl, pyridinium and pyrrole groups has been synthesized. The interaction between G and a series of cucurbit[ n ]urils (TMeQ[6], Q[7], Q[8], Q[10] ), has been studied both in aqueous solution and in the solid state. The binding interaction site between G and the Q[ n ] can be controlled by the size of the cavity of the Q[ n ]s. In the case of TMeQ[6], the benzyl is accommodated within the cavity, whilst for Q[7] and Q[8], the pyrrole ring and the benzyl are accommodated within the cavity of the Q[7/8], and the latter can shuttle on the guest G in a state of dynamic equilibrium. For the larger cavity of Q[10], the entire G molecule is located within the cavity of the Q[10] .